Konflik Etnis Dayak dan Madura dalam Masalah Hutan Kalimantan : Perspektif Green Thought - Mumtazinur Mumtazinur (Universitas Islam Negeri Ar-Raniry, 2017)
This article is an effort to explain the correlation between natural Resources and conflict that involved Dayak and Madura ethnic in Kalimantan. This writing begins by a brief description of ethnicity and conflict and also a glance of natural Resources. This article also describing conflict of ethnic about forest issue in Kalimantan through Green Thought. This perspective discern the logical correlation between living Environment and conflict emergence.